Biochemical effects of statins on lipid parameters among newly diagnosed dyslipidaemia subjects in primary care - Meor Anuar Shuhaili, Meor Fairuz Rizal; Samsudin, Intan Nureslyna; Chew, Boon How; Abdul Rahman, Hejar; Stanslas, Johnson; Sumon, Md. Shariful Hasan; Ahmad, Zalinah; Chellappah Thambiah, Subashini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Statins have several pleiotropic effects including its primary effect of lipid lowering that is important to prevent cardiovascular disease (CVD). Subjects often have heterogeneous responses to statin. This study aims to determine the biochemical effects of statins on lipid parameters among newly diagnosed dyslipidaemia subjects. Methods: This was a prospective observational study involving 118 newly diagnosed adults with dyslipidaemia from three government health clinics in Selangor, Malaysia. Biochemical analyses including fasting lipid profile [triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C)] and apolipoproteins (apoA1, apoB) were taken at baseline and follow-up after a month on statin. Results: Majority of subjects (61.9%) were prescribed with lovastatin, with the rest on simvastatin. At baseline, the median values for all lipid profile parameters (TC, LDL-C, HDL-C) and non-conventional lipid parameters (LDL-C:HDL-C ratio, non-HDL-C, TC:HDL-C ratio, apoB:apoA1 ratio) were deranged except for TG and apoA1. On follow up, all parameters showed median values within the reference range except for HDL-C, non-HDL-C and TC:HDL-C ratio. There was significant difference in the effect of statins on lipid parameters including predictors of cardiovascular risk, simvastatin having better effects. Conclusions: Different statins have varying effects on lipid parameters. Simvastatin showed significantly better effects compared to lovastatin. Non-HDL value should be included in the standard lipid profile report given its ease of use and implementation as it’s both a marker of coronary artery disease (CAD) risk stratification as well as an established determinant of goal attainment during therapy.